Seasonal crop diversity and its role in agricultural sustainability and food security in Afghanistan - Mohammadi, Nazir Khan (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Crops are the cornerstone of human nutrition, economic development, and agricultural sustainability. The classification of crops into Kharif, Rabi, and Zaid based on their growing seasons reflects the importance of seasonal planning for optimizing agricultural productivity. Kharif crops, including rice, maize, and cotton, are usually sown at the beginning of the monsoon rainy season and harvested at the end of the rainy season. Rabi crops such as wheat, mustard, and peas grow during the cooler winter months, while Zaid crops such as watermelon and cucumber grow during the transition period between Rabi and Kharif. The success of these cropping systems depends on multiple agro-ecological factors, including climate, soil type, irrigation conditions, and seed varieties. Advances in irrigation technology, pest and disease management, and high-yield crop varieties have significantly increased food production capacity and strengthened resilience to climate change. In addition, strategically selecting and rotating crops not only improves soil fertility and reduces pest and disease pressure, but also supports livestock rearing in mixed farm systems, especially in regions such as Afghanistan. Crops not only ensure nutrient availability but also drive rural employment and export opportunities. However, challenges such as climate change, land degradation, and water scarcity threaten continued production. Therefore, it is crucial to combine traditional practices with modern technologies and policy support.